Evaluating the Ameliorative Potential of Quercetin against the Bleomycin-Induced Pulmonary Fibrosis in Wistar Rats - Verma, Ramesh; Kushwah, Lokendra; Gohel, Darpesh; Patel, Manish; Marvania, Tulsi; Balakrishnan, Suresh (Pulmonary Medicine, 2013)
The current study deals with the effect of a dietary flavanoid quercetin on fibrotic lung tissue in rats. Bleomycin was administered by single intratracheal instillation to Wistar rats to induce lung fibrosis. The pathologies associated with this included significantly reduced antioxidant capacity, ultimately leading to protracted inflammation of the lung tissue. The hallmark of this induced fibrosis condition was an excessive collagen deposition in peribronchial and perialveolar regions of the lung. Oral quercetin treatment over a period of twenty days resulted in significant reversal of the pathologies. The antioxidant defense in lung tissue was revived. Moreover, activity of the collagenase MMP-7, which was high in fibrotic tissue, was seen restored after quercetin administration. Trichome staining of lung tissue sections showed high collagen deposition in fibrotic rats, which may be a direct result of increased mobilization of collagen by MMP-7. This was appreciably reduced in quercetin treated animals. These results point towards an important protective role of quercetin against idiopathic lung fibrosis, which remains a widely prevalent yet incurable condition in the present times.